(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
In this article, the effectiveness of adsorption techniques in removing arsenic(As) and lead(Pb) ions from the typical heavy metals contaminated surface (Tac) of the Aponmu River at different pH values (7.2, 6.4, 3.2 and 11.5) was determined using powdered eggshell. The initial dosage of selected water characteristics (pH, dissolved Oxygen, chloride, suspended solids, turbidity, As, dissolved oxygen (DO), Pb, and chemical oxygen demand (COD)) of the raw water was determined. The findings established that the average dosages of the selected pollutants were 6.48, 88.73 mgl-1, 255.67 mgl-1, 97.44 mgl-1, 290.44 NTU, 0.79 mgl-1, 0.55 mgl-1, 3.71 mgl-1 and 188.36 mg-1, for pH, dissolved Oxygen, chloride, suspended solids, turbidity, As, Pb, DO, and COD, respectively. In the case of adsorption, Pe was able to remove 99.98 % and 99.99 % of As and Pb dosage, respectively. Adsorption kinetics were in the range of 0.12878 and 0.37051, 0.0782 and 0.31757 for As and Pb respectively. It was concluded that adsorption mechanisms for these selected toxic pollutants (As and Pb) were mainly ion exchange and precipitation.